Nanotechnology in Construction 2015
DOI: 10.1007/978-3-319-17088-6_20
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nano-SiO2 on Cement Hydration

Abstract: The nanoparticles of SiO 2 with a size range of 5-20 nm were synthesized in acidic and basic medium from tetraethoxysilane (TEOS) using sol-gel method. The effect of agglomerated nanoparticles on the hydration of portland cement systems was analyzed by X-Ray Diffraction technique. Experimental results demonstrate that developed nano-SiO 2 produced in acidic medium accelerate the hydration by creating nuclei sites for the formation of C-S-H, whereas the nano-SiO 2 produced in basic medium reacted like a pozolan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The porosity of cement matrix has been thoroughly studied [234] at a mesoscopic structure of C-S-H level that reflects the properties of the macroscopic structure. Silica nanoparticles have been experimentally investigated to modify the cement matrix [235][236][237]. It was concluded that the calcium leaching could be controlled by silica nanoparticles.…”
Section: Understnading and Developing C-s-hmentioning
confidence: 99%
“…The porosity of cement matrix has been thoroughly studied [234] at a mesoscopic structure of C-S-H level that reflects the properties of the macroscopic structure. Silica nanoparticles have been experimentally investigated to modify the cement matrix [235][236][237]. It was concluded that the calcium leaching could be controlled by silica nanoparticles.…”
Section: Understnading and Developing C-s-hmentioning
confidence: 99%